Synthesis of benzopentathiepin analogs and their evaluation as inhibitors of the phosphatase STEP - Baguley, Tyler D. (Bioorg Med Chem Lett, 2015)
Striatal-enriched protein tyrosine phosphatase (STEP) is a brain specific protein tyrosine phosphatase that has been implicated in many neurodegenerative diseases, such as Alzheimer’s disease. We recently reported the benzopentathiepin TC-2153 as a potent inhibitor of STEP in vitro, cells and animals. Herein, we report the synthesis and evaluation of TC-2153 analogs in order to define what structural features are important for inhibition and to identify positions tolerant of substitution for further study. The trifluoromethyl substitution is beneficial for inhibitor potency, and the amine is tolerant of acylation, and thus provides a convenient handle for introducing additional functionality such as reporter groups.